EVALUASI TERHADAP RUMUSAN RANCANGAN UNDANG-UNDANG PESANTREN DAN PENDIDIKAN KEAGAMAAN - Binsar Antoni Hutabarat (Societas Dei: Jurnal Agama dan Masyarakat, 2018)
ABSTRACT: This article entitled, “Evaluation to the Formulation of the Bill on Islamic Boarding School and Religious Education” focuses on the evaluation to the formation process and the material of the Bill on Pesantren (Islamic Boarding School) and Religious Education. The instrument used is the Law of Regulation on Drafting the Law No. 12 of 2011 on Establishment of Laws and Regulations as well as the Ministerial Regulation from the State Minister for State Apparatus Reform No.: Per/04/M.PAN/4/2007 about General Guidance on Formulation, Implementation, Work Evaluation, and Revision of Public Policy in Central and Regional Government Institutions especially in relation with the principle of public policy formulation. This study finds that the Bill on Pesantren and Religious Education is elitist and has not fulfilled the requirement of policy formulation in democratic model. And the material of the Bill on Pesantren and Religious Education as an alternative policy has not fulfilled the principle of justice and diversity as decreed in the Regulation on Drafting the Law. The writer’s recommendation is that the proposed Bill on Pesantren and Religious Education as an alternative policy needs to be cancelled. KEYWORDS: public policy, pesantren (Islamic boarding school), religious education, policy evaluation